Guidance on Writing Literary Works for Students as Support for the School Literacy Movement - Wulandari, Patricia (HM Publisher, 2021)
Community empowerment program in literacy aims to provide training and coaching in writing literary works for students. This activity is an effort to foster students' critical literacy skills, primarily through writing skills. Also, this activity is a way to bring schools and students closer to literature. The implementation method, Community Service, is carried out by providing training and mentoring on an ongoing basis. The training is conducted for three days for students. This training is carried out in two ways, namely in-class and outclass. In-class training is conducted to provide students with the same understanding of writing literary works. Simultaneously, outclass training is conducted to hone students' sensitivity, critical power, and intuition to capture any existing problems around them to be used as a material in writing literary works. Likewise, with students' writing skills increasing and better, this is evidenced by the results of literary works that they make in the form of an anthology of poetry. The poems they made was varied in typography, theme, and contents. The students were enthusiastic and enthusiastic in participating in the activity. The activities of fostering literary writing in schools can help students and school parties better recognize literacy, especially in literary works' authorship. On the other hand, fostering the writing of literary works in schools can help teachers form the School Literacy Programme in their respective schools, bearing in mind is still very important in the school environment, so there is a need for sweet activities to increase student competency and love in reading and writing.